Прогнозування індексу споживчих цін в Україні з використанням регресійних моделей і фільтра Калмана - Karayuz, I. V.; Bidyuk, P. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2015)
The paper considers the problem of short term forecasting of consumer price index using regression models and adaptive Kalman filter. The main purpose of the study is constructing of high quality model for forecasting of consumer price index and application of Kalman filter for computing optimal estimates of states for the process under investigation. The basic results of the study are as follows: two modifications of the Kalman filter (ordinary and adaptive), directed towards estimation of covariances for stochastic state disturbances and measurement errors. Alternative short term forecasts are generated with regression models and Kalman filters. A comparative analysis of results achieved is given. The necessary statistical data was taken from Ukrainian economy in transition.